PENGARUH PROFITABILITAS, LEVERAGE DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE (Studi Pada Perusahaan Manufaktur sub sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2019-2022) - Lia Awaliah; Ika Sari (Jurnal Cakrawala Ilmiah, 2025)
This study aims to determine the effect of Profitability, Leverage, Sales Growth on Tax Avoidance in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2022 period. The method used in this study is a descriptive method with a quantitative approach. With a total sample population of 16 companies using a purposive sampling technique. Data collection and analysis methods used in this study used the Statistical Product and Service Solution (SPSS) 26 program. The results of this study indicate that Profitablility has an effect on Tax Avoidance, Leverage does not have effect on Tax Avoidance, Sales Growth has an effect on Tax Avoidance.